Defining the Threshold IL-2 Signal Required for Induction of Selective Treg Cell Responses Using Engineered IL-2 Muteins - Ghelani, Aazam; Bates, Darren; Conner, Kip; Wu, Min-Zu; Lu, Jiamiao; Hu, Yi-Ling; Li, Chi-Ming; Chaudhry, Ashutosh; Sohn, Sue J. (Frontiers in Immunology, 2020)
Among all T and NK cell subsets, regulatory T (Treg) cells typically respond to the lowest concentrations of IL-2 due to elevated surface expression of the IL-2R alpha chain (CD25) and the high affinity IL-2 receptor (IL-2R) complex. This enhanced sensitivity forms the basis for low-dose (LD) IL-2 therapy for the treatment of inflammatory diseases, where efficacy correlates with increased Treg cell number and expression of functional markers. Despite strong preclinical support for this approach, moderate and variable clinical efficacy has raised concerns that adequate Treg selectivity still cannot be achieved with LD IL-2, and/or that doses are too low to stimulate effective Treg-mediated suppression within tissues. This has prompted development of IL-2 variants with greater Treg selectivity, achieved through attenuated affinity for the signaling chains of the IL-2 receptor (CD122, CD132) and, consequently, greater reliance on high CD25 levels for full receptor binding and signaling. While certain IL-2 variants have advanced to the clinic, it remains unknown if the full range of IL-2R signaling potency and Treg-selectivity observed with low concentrations of wildtype IL-2 can be sufficiently recapitulated with attenuated IL-2 muteins at high concentrations. Using a panel of engineered IL-2 muteins, we investigated how a range of IL-2R signaling intensity, benchmarked by the degree of STAT5 phosphorylation, relates to biologically relevant Treg cell responses such as proliferation, lineage and phenotypic marker expression, and suppressor function. Our results demonstrate that a surprisingly wide dynamic range of IL-2R signaling intensity leads to productive biological responses in Treg cells, with negligible STAT5 phosphorylation associating with nearly complete downstream effects such as Treg proliferation and suppressor activity. Furthermore, we show with both in vitro and humanized mouse in vivo systems that different biological responses in Treg cells require different minimal IL-2R signaling thresholds. Our findings suggest that more than minimal IL-2R signaling, beyond that capable of driving Treg cell proliferation, may be required to fully enhance Treg cell stability and suppressor function in vivo.